Payment of Insurance Premium and Subsistence of the Insurance Contract - Ortega Piana, Marco Antonio (2015)
This article addresses the issue referred to the remedies of the insurance contract for the non-payment of the premium. t hrough an analysis of the previous and current legislation, the author examines the consequences of the non-payment of the insurance premium in the contractual relationship. By recognizing the protective nature of the legislation in favor of the insured as the weak party, three specific contractual remedies are identified: The suspension of coverage, the termination of the contract and the the extinction of the contractual relationship by inaction of the parties.